Intravascular Papillary Endothelial Hyperplasia (Masson tumor) of the Skull : Case Report and Literature Review - Park, Keuk Kyu (The Korean Neurosurgical Society, 2012)
A 10-year-old female patient presented with a rapidly growing nodular mass lesion on her right frontal area. On skull radiography and computed tomography (CT) imaging, this mass had a well-demarcated punch-out lesion with a transdiploic, exophytic soft tissue mass nodule on the frontal scalp. Magnetic resonance (MR) imaging revealed the presence of a 1.5×1.2×1 cm sized calvarial lesion. This lesion was hypointense on T1 and heterogenous hyperintense on T2 weighted MR images, and exhibited heterogeneous enhancement of the soft tissue filling the punch-out lesion after intravenous administration of gadolinium. En block removal of the tumor with resection of the rim of the normal bone was performed. The pathological diagnosis was intravascular papillary endothelial hyperplasia (IPEH). After surgery, no recurrence was found for 8 months. IPEH is a rare and benign reactive lesion usually found in thrombosed subcutaneous blood vessels. Involvement of skull bone is rare. In this article, we present a case of IPEH involving the calvarium, in a 10-year-old woman.